Corruption and Political Participation in Hungary: Testing Models of Civic Engagement. Issue 3 (August 2019) - Kostadinova, Tatiana; Kmetty, Zoltán
Extant literature concludes that corruption may have a devastating effect on economic growth and institutional trust in transitional democracies, but scholars remain divided on how malfeasance influences political behavior. In this article, we explore the likelihood of a mobilization effect of corruption in a post-communist setting. We argue that the indicators used in previous scholarship on corruption vary in important ways and may affect citizen incentives for participation differently. In particular, we hypothesize and then assess whether actual experience with bribery, perceptions of widespread corruption, and concerns about increase of corruption in the future encourage individuals to engage in different sets of activities. Original data from a 2014 post-election survey in Hungary are used for empirical tests of several regression models. Our findings suggest that the type of corruption assessment is important for the specific political activity in which a citizen would engage.